2007
DOI: 10.1242/jcs.03452
|View full text |Cite
|
Sign up to set email alerts
|

The role of GW/P-bodies in RNA processing and silencing

Abstract: There was an error published in J. Cell Sci. 120, 1317-1323.We apologise for two errors that occurred in the online and pdf versions of this article. The printed version is correct.On p. 1317, in the Summary, the sentence 'Formation of GW bodies appears to depend on both specific protein factors and RNA, in particular, microRNA.' appeared twice. The correct version of the summary is shown below. Summary GW bodies, also known as mammalian P-bodies, are cytoplasmic foci involved in the post-transcriptional regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 0 publications
0
40
1
Order By: Relevance
“…Similarly, GFP-fused DCP1 (a P-body component) was constructed and co-transfected into cultured cells with siRNA, displaying the spatial relationship between transfected siRNA and P bodies. In contrast to studies showing that transfected siRNA colocalizes with RISC and P bodies (Liu et al 2005a(Liu et al ,2005bBerezhna et al, 2006;Pauley et al, 2006;Jakymiw et al, 2007), confocal imaging as well as quantitative analysis in the present study revealed that the siRNA aggregated into cytoplasmic granules that are distinct from RISC or P bodies (Fig. 1).…”
Section: Localization Of Transfected Sirna In Non-p-body Granulescontrasting
confidence: 99%
“…Similarly, GFP-fused DCP1 (a P-body component) was constructed and co-transfected into cultured cells with siRNA, displaying the spatial relationship between transfected siRNA and P bodies. In contrast to studies showing that transfected siRNA colocalizes with RISC and P bodies (Liu et al 2005a(Liu et al ,2005bBerezhna et al, 2006;Pauley et al, 2006;Jakymiw et al, 2007), confocal imaging as well as quantitative analysis in the present study revealed that the siRNA aggregated into cytoplasmic granules that are distinct from RISC or P bodies (Fig. 1).…”
Section: Localization Of Transfected Sirna In Non-p-body Granulescontrasting
confidence: 99%
“…MicroRNAs bind to complementary sequences in the 3′UTRs of target mRNAs, (Bartel, 2004(Bartel, , 2009 resulting in negative regulation (transcript degradation and post-translational suppression) (Jakymiw et al, 2007;Lim et al, 2005;Wu et al, 2006). MicroRNAs may also bind to the non-coding regulatory regions in gene promoters, sometimes leading to positive regulation (transcriptional and translational activation) (Li et al, 2006;Mao et al, 2008;Place et al, 2008;Suzuki and Kelleher, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These percentages of mRNAs as predicted targets of miRNA are within the range reported in the literature (10-60%). (Friedman et al, 2009) Although translational repression is the main mechanism by which miRNA suppresses expression in mammalian cells, the suppressed target mRNA is often eventually degraded in cellular Processing bodies (P-bodies) (Jakymiw et al, 2007;Lim et al, 2005;Wu et al, 2006). Thus increases of miRNAs often lead to decreases of potential target mRNAs.…”
Section: Correspondence Between Over-expressed Mrnas and The Underexpmentioning
confidence: 99%
“…Glycine/tryptophan/processing bodies Glycine/tryptophan (GW) bodies (GWBs) are 30-100 mm cytoplasmic structures containing a GW-rich mRNA binding protein GW182 (reviewed in [107]). They are sites for mRNA processing and degradation, and are important in the RNA interference (RNAi) pathway (reviewed in [107,108]).…”
Section: Mitochondriamentioning
confidence: 99%
“…They are sites for mRNA processing and degradation, and are important in the RNA interference (RNAi) pathway (reviewed in [107,108]). The most common diagnoses of patients with autoantibodies to components of GWBs included neuropathies ($33%), SjS ($30%), and SSc ($15%), including an overlap with PBC (R. Bhanji, T. Eystathioy, E.K.L.…”
Section: Mitochondriamentioning
confidence: 99%